Vendor payment system: a case study of Petronas Dagangan Berhad, Kuantan / Nurhazwani Sudari - Sudari, Nurhazwani (Faculty of Business and Management, 2009)
Payment systems are moving from being a narrow channel for transferring funds to a much wider integrated network for transferring additional forms of value. This research found about a vendor payment system in PETRONAS Dagangan Berhad Kuantan. The issue of this study is time revolve around processing time taken to make payment to their vendor. The researcher’s task is to needs to identify the current payment method made vendor in PETRONAS Dagangan Berhad Kuantan, its relevant problem and suggest a PDB Kuantan. Nowadays, there are many types of payment that organization can apply and made their business easier and run smoothly. In the early days, PETRONAS Dagangan Berhad Kuantan uses cheques because it is high security compared to other payment method. Moreover, these kinds of payment method are very popular among the business and individual. This method has been practiced by PETRONAS Dagangan Berhad Eastern to made payment to their vendors. Method of payment used in this researcher is through personal interview. The respondents are selected randomly in order to make personal interview. The researcher also indirectly used informal interview with another employees during free time. The set of question was design to find out and match to the objective of the study. The researcher suggests and recommends PETRONAS Dagangan Berhad Kuantan to apply new Automated Payment System which can increase their payment efficiency to their vendors. This new payment system will give many benefits to the organization and at the same time payments to the vendors become more efficient.